A study of continuous monitoring of endotracheal tube cuff pressure using an electronic device in critical care setting - Khairuddin, Ismail (2009)
The endotracheal tube (ETT) cuff pressure measurement is not a routine practice in many critical care units. The main purpose of this study is to determine the accuracy or relationship of electronic measurement of ETT cuff pressure by continuous method (using aneroid manometer method as the control) and the usefulness of the continuous method toward reducing endotracheal tube-related complications in intensive care settings. A total of 56 patients were recruited involving ICU patient intubated with ETT with cuff. A preliminary study was also conducted to determine the safety and stability of this electronic device. The precision of reading of ETT cuff pressure were compared with manual aneroid manometer and the variability of cuff pressure changes were also assessed apart from ETT cuff related complications. The complications that we looked for were the prevalence of ventilator-associated pneumonia (V AP), post-extubation stridor, sore-throat and endotrachealtube (ETT) dislodgement. We found that there was a significant correlation between the readings by aneroid manometer with that of electronic measurement device, with p value of< 0.001 ( mean 44.16 vs 44.22 mm Hg ). The prevalence of V AP, sore-throat and endotracheal tube dislodgement were 1.8%, 3.6% and 3.6% respectively. No patient was noticed to have post-extubation stridor. The readings recorded by the electronic device for ETT cuff measurement was comparable with aneroid manometer and its use could potentially reduce ETT cuff-related complications.